PERSEPSI IBU RUMAH TANGGA TERHADAP PERAN GENDER PADA TAYANGAN SINETRON “DUNIA TERBALIK” RCTI - Muhammad Yusuf AR; Atia Vitalia Aswadany (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
Television programs present something to be liked. In addition, it must also give a message that brings influence to life in society. The problem of this research is how the housewives' perception of Gamtufkange Urban Village on gender roles in the Reverse World comedy soap opera on RCTI, with the aim of Knowing the perception of Gamtufkange Urban Housewives towards gender roles in the comedy of Reverse World comedy. This research uses a qualitative approach. With primary data sources from informant interviews and secondary data. Data were analyzed using five factors that influence perceptions according to Deddy Mulyana, namely perceptions based on experience, perceptions are selective, perceptions are presumptive, perceptions are evaluative and perceptions are contextual. The theoretical foundation used in this study is the Stimulus-Organism-Response Theory. The results of the study concluded that some housewives disagreed with the role of gender in the soap opera "Reverse World" by reason of their irregularities and cultural and religious norms. Men do not deserve the role that should be done by women in the home. While housewives who agreed to gender roles in the soap opera shows reasoned, a wife working to help their husbands was not taboo and could be accepted. The wife can work to help the family economy, but still must be responsible for taking care of the family.